Effect of osmoprotectants on performance of wheat (Triticum aestivum) under terminal heat stress condition of North-West India - SURYAVANSHI, P; BUTTAR, G S; BRAR, A S (The Indian Journal of Agricultural Sciences, 2016)
Field experiment was conducted during rabi season of 2013-14 and 2014-15 at Ludhiana to evaluate the effect of various osmoprotectants on productivity of wheat (Triticum aestivum L.) under terminal heat stress condition. Results revealed that during 2013-14, foliar application of sodium nitroprusside 400 μg/ml, 2% KNO3 and thiourea 20 mM recorded higher plant height, leaf area index and dry matter accumulation at harvest over the unsprayed and water sprayed control. Grain yield also increased to the extent of 18.8% by foliar application of sodium nitroprusside 400 μg/ml, 17.9% by 2% KNO3 and 14.9% by thiourea 20 mM during 2013-14. Injury to wheat plant was observed due to higher doses of osmoprotectants. SNP 1 200 μg/ml and thiourea 60 mM decreased yield by 3.03% and 2.30% over the unsprayed control. During excessive wet season of 2014-15, SNP 800 μg/ml, 3% KNO3 and thiourea 40 mMperformed better as compared to lower doses.